Predictability of Stock Returns in Central and Eastern European Countries - Pietraszewski, Piotr (Acta Universitatis Lodziensis. Folia Oeconomica, 2022)
Stock return predictability in highly developed countries has both empirical and theoretical justification in financial literature. The article aims to answer the question if market valuation ratios that relate share prices to various accounting quantities have any predictive power for long‑term stock index returns on investments in capital markets of some Central and Eastern European countries, namely the Czech Republic, Hungary, Poland, and Russia. Heteroskedasticity and autocorrelation‑consistent estimators with a small‑sample degrees of freedom adjustment were used in regressions to track the overlapping data problem and small sample bias. The results of an investigation show that some of these ratios, such as price to a ten‑year moving average of real earnings, commonly known as the cyclically adjusted price earnings (CAPE) ratio, price to estimated profits, market to book value and price to sales revenues have a strong predictive power for cumulative returns mainly over long horizons. On the other hand, price to one‑year earnings, dividend yield or price to cash flow ratios prove to be quite poor predictors. Following the arguments of behavioural finance, we conclude that the evidence obtained in the study proving a fairly significant link between current values of market ratios and future cumulative returns indicates a certain degree of ineffectiveness of the analysed markets during the examined period.